Propuesta de aprovechamiento turístico del Río Daule, Cantón Balzar Provincia del Guayas, Año 2022 - Chávez Rizo, Fátima Jamileth (2022)
The present research was carried out in the Canton Balzar belonging to the province of Guayas, with the aim of designing a proposal for tourist use in the Daule River, due to the lack of tourist offer that this canton has, so methods such as bibliographic, statistical, quantitative, descriptive and techniques such as the survey and the field visit were used where the expected results were